Az államhatalmi ágak elválasztása az ókortól a XIX. század második feléig - Csűrös, Gabriella (Debreceni Jogi Műhely, 2007)
The purpose of my study is to examine the theories of the separation of powers and its application in different periods. My investigation based on two monograph from Bibó: The Principle of the Separation of Power Sometime and at Present, and Lawfull and Effective Administration, Firm Executive Power. The ancient philosophers have already dealed with such theories. Among of them Aristoteles has the largest importance defining the three main powers: the legislation, the executive power, and the iurisdiction. The most substantial step in the Middle Ages was creating the moral basis for exercise of powers. The reformation and the development of civil society has improved this conception, Montesquieu attributed the powers with function, and emphasized the separation of them. Nevertheless István Bibó emphasizes not only the separation, but also the struggle against the concentration of power, and the abuse of power. The principle of the separation of powers could prevail clearly only in the USA, but not in Europe. István Bibó explains the causes of those in his monograph (The Principle of the Separation of Power Sometime and at Present).,for example the function of the monarcha or the principle of sovereignty. Bibó defined the obstructive factors in realisation of the principle of the separation of powers. These are: bureaucracy and the exorbitant state role in the economic and in the culture. In his other monography (Lawful and Effective Administration, Firm Executive Power) Bibó describes the necessary elements of lawful and effective administration, like loyality, professionalism and effective enforcement. At the same time, by realisation of these, the risk of the abuse of power could arise, creation of a new power would be therefor necessary. This power might be a regulatory power, which would be able to define the main criteria of exercise of power. Beforehand the church played that role, but in the twentieth century its function became vacant. I think the function of the new power would be similar to the role of the Constitutional Court at national level, or to the role of the European Court of Justice, of the International Court of Justice, and of the International Criminal Court at international level.